Comparison of the Deep Optic Nerve Structures in Superior Segmental Optic Nerve Hypoplasia and Primary Open-Angle Glaucoma. Issue 8 (August 2016) - Lee, Eun Ji; Lee, Kyoung Min; Lee, Seung Hyen; Kim, Tae-Woo
Abstract : Purpose: The purpose of this study was to characterize the microstructure of the deep optic nerve tissues in eyes with superior segmental optic nerve hypoplasia (SSOH) in comparison with that in primary open-angle glaucoma (POAG). Methods: Thirty-five eyes with SSOH, 37 eyes with POAG, and 54 healthy control eyes underwent enhanced depth imaging (EDI) volume scanning of the optic nerve using spectral-domain optical coherence tomography (SD-OCT). POAG patients were matched with SSOH patients in terms of the thickness of the neuroretinal rim and the retinal nerve fiber layer in the superior sector. The lamina cribrosa thickness (LCT) was determined in 3 equidistant planes, and anterior lamina cribrosa surface depth (LCD) was determined in 5 equidistant planes. The measurements were compared between groups, and the areas under the receiver operating characteristic curves (AUC) were obtained for each parameter. Results: Eyes with SSOH had larger LCT and smaller LCD than POAG eyes at all locations (all P <0.001). The largest LCT was observed at the superior midperiphery in the SSOH group, but at central locations in both the POAG and control groups. The best parameters for discriminating the SSOH from glaucoma and healthy eyes were the superior midperipheral LCT (AUC=0.973) and inferior and inferior midperipheral LCD (AUCs=0.906), respectively. Conclusions: The LCT and LCD exhibited characteristic features in eyes with SSOH that were distinctive from those of POAG and healthy eyes. Investigation of the deep optic nerve structure using EDI SD-OCT may be beneficial for differentiating between SSOH and glaucoma, which may help to avoid both overtreatment and undertreatment.